Differences in Clinical Aspects Between Subacute Thyroiditis Associated with COVID-19 Vaccines and Classical Subacute Thyroiditis - Topaloğlu, Ömercan; Tekin, Sakin; Topaloğlu, Seda Nur; Bayraktaroglu, Taner (Hormone and Metabolic Research, 2022)
Subacute thyroiditis (SAT) developed after SARS-CoV-2 vaccines has been less studied. We aimed to compare classical SAT and SAT developed after SARS-CoV-2 vaccines in the context of clinical aspects. Adults with SAT detected in 90 days of COVID-19 vaccination (CoronaVac or Pfizer/BioNTech) were grouped as Vac-SAT. Those with a history of SARS-CoV-2 or upper respiratory tract infection in 6 months before the vaccination, or vaccination with another antiviral vaccine after COVID-19 vaccination were excluded. Those with SAT detected before COVID-19 pandemic were grouped as Classical-SAT. Of total (n=85), female/male (54/31) ratio and age [43 (23–65)] were similar in Vac-SAT (n=23) and Classical-SAT (n=62). Duration between vaccine and SAT was 45 (7–90) days, and similar in CoronaVac-SAT (n=5) and BioNTech-SAT (n=18). SAT-duration was 28 (10–150) days, and higher in Vac-SAT than in Classical-SAT (p=0.023). SAT was developed after the 1st dose vaccine in minority in CoronaVac-SAT (n=2) and BioNTech-SAT (n=3) (p=0.263). Previous LT4 use, and TSH elevation after resolution were more frequent in Vac-SAT than in Classical-SAT (p=0.027 and p=0.041). We included a considerable number of patients with SAT occurred after COVID-19 vaccines. We cannot provide clear evidence regarding the association of COVID-19 vaccines with SAT. SAT associated with CoronaVac or BioNTech seems unlikely to be occurred after the 1st dose, and to have a longer duration, more likely to be associated with previous LT4 use and lead TSH elevation after resolution than Classical-SAT. TSH should be followed-up after the resolution of SAT detected after COVID-19 vaccination.
Keywords: subacute thyroiditis; vaccine; thyroiditis; COVID-19; COVID-19 vaccine; SARS-CoV-2